2015
DOI: 10.1136/bjophthalmol-2015-306781
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of plasma vascular endothelial growth factor concentrations during aflibercept loading phase and after the transition to bimonthly treatment for neovascular age-related macular degeneration

Abstract: Identifier no. NCT02125864.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Roald et al used intravitreal aflibercept to treat 16 individuals with naïve neovascular macular degeneration. 34 To summarize, aflibercept significantly reduced the plasma VEGF levels (which was 56% on the first day) immediately after the treatment. Despite the monthly intravitreal injection of aflibercept, plasma VEGF levels were 87% of baseline in the first month and 90% in the second month.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Roald et al used intravitreal aflibercept to treat 16 individuals with naïve neovascular macular degeneration. 34 To summarize, aflibercept significantly reduced the plasma VEGF levels (which was 56% on the first day) immediately after the treatment. Despite the monthly intravitreal injection of aflibercept, plasma VEGF levels were 87% of baseline in the first month and 90% in the second month.…”
Section: Discussionmentioning
confidence: 82%
“…We found that the mean VEGF level of the control group was statistically higher than those of the injection groups, whereas no statistically significant differences were noted between the injected groups. 34 To summarize, aflibercept significantly reduced the plasma VEGF levels (which was 56% on the first day) immediately after the treatment. Despite the monthly intravitreal injection of aflibercept, plasma VEGF levels were 87% of baseline in the first month and 90% in the second month.…”
Section: Discussionmentioning
confidence: 82%
“…The mechanism or reason for this underestimation was not determined. A separate study [19], which used a different methodology to measure free VEGF (Bio-Plex Cytokine VEGF-A Luminex assay [Bio-Rad]), reported less impact on circulating VEGF after IVT administration of 2 mg aflibercept, (500 pg/ml) of VEGF with increasing concentrations of each inhibitor, ranging from 72.9 to 2.7 pM, were prepared and incubated at room temperature for approximately 3 days before analysis using the Quantikine VEGF ELISA. At the detection step, the anti-VEGF polyclonal antibody detection antibody in the kit was replaced with an anti-human IgG, Fcγ fragment-specific, polyclonal antibody (for aflibercept and bevacizumab) or an antihuman IgG, F(ab') 2 fragment-specific, polyclonal antibody (for ranibizumab).…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study [19], using a different methodology to measure VEGF, only a modest and temporary decrease in circulating VEGF concentration was observed in 16 patients after IVT administration of 2 mg aflibercept. In this study, the mean free VEGF concentration was 59.6 pg/ml at baseline and only decreased to 32.5 pg/ml after administration of aflibercept.…”
mentioning
confidence: 90%
“…Aflibercept was also the most potent of these three drugs in reducing plasma-free VEGF with levels undetectable from 3 hours postdose to greater than 1 week postdose. 71 It is postulated that the Fc fragment present in both the bevacizumab and aflibercept molecules extends their serum half-life, accounting for these differences. 72 The clinical significance of this is, however, yet to be elucidated.…”
Section: Pharmacokineticsmentioning
confidence: 99%